ANALISIS YURIDIS MEKANISME PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL (DALAM KERANGKA GATT-WTO) - Ukas Ukas (JCH (Jurnal Cendekia Hukum), 2018)
The dispute settlement mechanism of the World Trade Organization and the General Agreement on Tariffs and Trade, is a document containing juridical elements, stated about the rights and obligations of the participating countries of the agreement explicitly, of course, often lead to disputes. GATT as an institution has implemented procedures and procedures to deal with disputes arising between participating countries, in the context of international law in general. The process in which the party to the dispute is encouraged to counsel and endeavor to settle the dispute among themselves, and or through the WTO. The formulation of the problem in this research is how the dispute settlement mechanism in international trade and the impact of what is caused in the international trade sector. The method used in this research is empirical juridical analysis, from existing data, with qualitative analysis approach. The point is that the settlement of disputes refers to the provisions and Articles contained in GATT 1947 with the stages of consultation and or the establishment of a panel. The impact associated with international trade is to facilitate import-export and create harmony in international trade between countries.